filmov
tv
y = x tanh^-1(x) + ln(sqrt(1 - x^2)), Find the derivative
![preview_player](https://i.ytimg.com/vi/7NQWpNiw3Jo/hqdefault.jpg)
Показать описание
y = x tanh^-1(x) + ln(sqrt(1 - x^2)), Find the derivative
Derivative of tanh^-1(x)
y = x tanh^-1(x) + ln(sqrt(1 - x^2)), Find the derivative
Find derivative of y= (1- x) tanh^(-1) x with respect to x. Inverse Hyperbolic Functions
Derivative of Inverse Hyperbolic Trigonometry: tanh^-1(x)
Find derivative of y= x tanh^(-1) x + ln sqrt(1- x^2). Inverse Hyperbolic Functions
Inverse Hyperbolic Trigonometry as Logarithms: tanh^-1(x)
prove that tanh(x+y)=tanhx+tanhy/1+tanhx tanhy
Inverse function of tanh x
#ThayThinhHoa12 | CÙNG THẦY THỊNH HÓA GIẢI CÁC BẢI TẬP HỮU CƠ 12
Inverse tanh(x)
Q15, derivative of tanh^-1(x)
tanh^-1x +tanh^-1y=tanh^-1[(x+y)÷1+xy]#Bidyadataganeshtutorial please subscribeif you satisfy
Differentiation Example with the Inverse Hyperbolic Tangent: y = tanh^(-1)(cos(x))
y = tanh^-1(sqrt(x)), Find the derivative
A-Level Further Maths H1-04 Hyperbolic Functions: Sketching y=tanh(x)
Find derivative for y = x coth(1+ x^2). Hyperbolic functions
Inverse Hyperbolic Tan is a 1/2 ln(1+x / 1-x)
Differentiation of inverse tanh (tanh^-1(x))
Prove that tanh⁻¹x + tanh⁻¹y = tanh⁻¹[ (x+y)/(1+xy)]
tanh(x+y) = (tanh x + tanh y)/(1+ tanh x tanh y) || Hyperbolic Trigonometric Identities
BSc S1- Proof of tanh^-1x (06/01/2021)
Graph of inverse hyperbolic tangent function | y=tanh^-1x | Domain | Range | Easy Method
Q16, derivative of x*tanh(x)+ln(sqrt(1-x^2))
Find derivative of y = sinh^(-1) (tan x) with respect to x. Inverse Hyperbolic Functions
Комментарии